Cost and outcome of a community-based paediatric hearing screening programme in rural India with application of tele-audiology for follow-up diagnostic hearing assessment. (3rd June 2018) - Ramkumar, Vidya; John, K. R.; Selvakumar, K.; Vanaja, C. S.; Nagarajan, Roopa; Hall, James W.
Abstract: Objective : This study evaluated the cost and outcome of a community-based hearing screening programme in which village health workers (VHWs) screened children in their homes using a two-step DPOAE screening protocol. Children referred in a second screening underwent tele diagnostic ABR testing in a mobile tele-van using satellite connectivity or at local centre using broadband internet at the rural location. Design : Economic analysis was carried out to estimate cost incurred and outcome achieved for hearing screening, follow-up diagnostic assessment and identification of hearing loss. Two-way sensitivity analysis determined the most beneficial cost-outcome. Study sample : 1335 children under 5 years of age underwent screening by VHWs. Results : Nineteen of the 22 children referred completed the tele diagnostic evaluation. Five children were identified with hearing loss. The cost-outcomes were better when using broadband internet for tele-diagnostics. The use of least expensive human resources and equipment yielded the lowest cost per child screened (Rs.1526; 23; €21). When follow-up expenses were thus maximised, the cost per child was reduced considerably for diagnostic hearing assessment (Rs.102, 065; 1532; €1368) and for the cost per child identified (Rs.388, 237; 5826; €5204). Conclusion : Settings with constrained resources can benefit from a community-based programme integrated with tele diagnostics.